2017
DOI: 10.1111/pbi.12800
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide identification of genes involved in the potato response to drought indicates functional evolutionary conservation with Arabidopsis plants

Abstract: SummaryPotato is one of the four most important food crop plants worldwide and is strongly affected by drought. The following two pairs of potato cultivars, which are related in ancestry but show different drought tolerances, were chosen for comparative gene expression studies: Gwiazda/Oberon and Tajfun/Owacja. Comparative RNA‐seq analyses of gene expression differences in the transcriptomes obtained from drought‐tolerant versus drought‐sensitive plants during water shortage conditions were performed. The 23 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 62 publications
1
39
0
Order By: Relevance
“…Considering the number of different mechanisms by which perturbations in water availability may affect potato yield in agronomic terms, in our study, we focused on the impacts of “meteorological droughts” (Wilhite & Glantz, ), which represent periods of precipitation deficiency, high temperatures and low humidity. To enhance our understanding of the physiology and genetics of resistance, drought resistance of potato cultivars was estimated on the basis of potato physiological responses to soil drought presented here as well as on the basis of comparative gene expression studies presented elsewhere (Pieczynski et al., ). Qualitative and quantitative global analyses of gene expression, carried out parallel to the physiological experiments on the same pairs of potato cultivars, gain more insight into genetic background of drought tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the number of different mechanisms by which perturbations in water availability may affect potato yield in agronomic terms, in our study, we focused on the impacts of “meteorological droughts” (Wilhite & Glantz, ), which represent periods of precipitation deficiency, high temperatures and low humidity. To enhance our understanding of the physiology and genetics of resistance, drought resistance of potato cultivars was estimated on the basis of potato physiological responses to soil drought presented here as well as on the basis of comparative gene expression studies presented elsewhere (Pieczynski et al., ). Qualitative and quantitative global analyses of gene expression, carried out parallel to the physiological experiments on the same pairs of potato cultivars, gain more insight into genetic background of drought tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The evolutionary conservation of the functions of the selected genes in the plant response to drought confirms their importance in the ability of potato plants to cope with water deficiency. Knowledge regarding functions of these genes seems to facilitate the genetic improvement of potato cultivar tolerance to unfavourable conditions (Pieczynski et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptome analysis showed that transcription factors, protein kinases, proteins related to redox regulation, carbohydrate metabolism and osmotic adjustment participate in the tolerance of potato to osmotic stress [8][9][10]. Twenty-three drought-responsive genes were identified by comparing the transcriptomes of drought-tolerant and drought-sensitive potato varieties under water stress, and seven homologous genes were identified by homozygous mutants of Arabidopsis thaliana, six of them including carbohydrate transporter, 2 of 17 mitogen-activated protein kinase kinase kinase 15 (MAPKKK15), serine-like carboxypeptidase 19 (SCPL19), armadillo/beta-catenin-like repeat-containing protein, high-affinity nitrate transporter 2.7 and nonspecific lipid transfer protein 2 (nsLPT) can improve the drought resistance of Arabidopsis [11]. These results suggest the complexity of the molecular mechanism of potato drought-resistance.…”
Section: Introductionmentioning
confidence: 99%